Research report of lifestyle, behavior and physical appearance of Metro Sexual Male students in UiTM Sabah - Mohamad, Muhd. Hilmi; Suwae, Rugayah; Berahim, Siti Noraishah; Masri, Siti Syazwani; Jasman, Zurimah (2009)
This study is about metrosexuai male students in UiTM Sabah. The main focus to be investigated is their lifestyle, behavior and physical appearance. The researchers put 3 main variables as a theory of the impact factors towards this type of male. The 3 main variables are personal variables (i.e. self-image consciousness, ageing effects, physical attractiveness, state of health), socio-cultural variables (i.e. beliefs, lifestyle), and marketing variables (i.e. advertising, purchase situation). The researchers use questionnaire in order to achieve the answer about this study. The respondents that will be reached is 100 respondents which all of them are UiTM male students. This study was done only for 3 months which started at the month of August until the month of October. Madam Sharifah Nurafizah is the guider of this research and 5 persons will do the research.